Association of long-term exposure to air pollution with chronic sleep deprivation in adults from 141 urban communities in South Korea: a community-level longitudinal study, 2008‒2016. (5th August 2021) - Lee, Whanhee; Seo, Daeun; Myung, Woojae; Prifti, Kristi; Kang, Cinoo; Jang, Hyemin; Park, Chaerin; Bell, Michelle L.; Kim, Ho
Abstract: Aims: It has been well known that air pollution and sleep deprivation individually have impacts on human health; however, the association between the two has not been well researched. The aim of this study was to investigate this relationship at a community level. Methods: We collected sleep outcomes from the Korean Community Health Survey between years of 2008 and 2016. The data contained 1 130 080 selected adults aged ⩾ 19 years, from 141 communities. As sleep outcomes, annual chronic sleep deprivation (% of people who sleep ⩽ 5 h per day on average) and average values of daily mean sleep duration were used. Community-specific annual averages of particulate matter with a diameter ⩽ 10 μm (PM10 ), nitrogen dioxide (NO2 ) and carbon monoxide (CO) were collected and then applied to a linear mixed effects model to estimate the association between air pollution over the past 4 years and sleep outcomes. Population density, green space, health behaviour, and gross regional domestic product per capita variables were considered as confounders in all mixed effect models. Results: From the linear mixed effect models, we found that the chronic sleep deprivation % was positively associated with PM10 (0.33% increase with 95% CI 0.05–0.60; per 10 μg/m 3 ) and NO2 (0.68% with 95% CI 0.44–0.92; per 10 ppm). Higher PM10 and NO2 were also associated with shorter sleep duration, with a reduction of 0.37 min (95% CI −0.33 to 1.07 min; per 10 μg/m 3 ) and 2.09 min (95% CI 1.50–2.68 min; per 10 ppm), respectively. The associations between PM10 and sleep outcomes were higher in females than males and in the older age groups (⩾ 60-years) than in younger age groups (19–39 and 40–59 years). However, the association between NO2 and sleep outcomes were more higher in males than in females and in the younger age groups (19–39 years) than other age groups. Conclusions: Our findings provide epidemiological evidence that long-term interventions to reduce air pollutions are anticipated to provide improvements in sleep deficiency.